Dietary supplementation with xylooligosaccharides and exogenous enzyme improves milk production, energy utilization efficiency and reduces enteric methane emissions of Jersey cows - Lifeng Dong; Lei Zhao; Bowei Li; Yanhua Gao; Tianhai Yan; Peter Lund; Zhuofan Liu; Qiyu Diao (Journal of Animal Science and Biotechnology, 2023)
Abstract Background Sustainable strategies for enteric methane (CH4) mitigation of dairy cows have been extensively explored to improve production performance and alleviate environmental pressure. The present study aimed to investigate the effects of dietary xylooligosaccharides (XOS) and exogenous enzyme (EXE) supplementation on milk production, nutrient digestibility, enteric CH4 emissions, energy utilization efficiency of lactating Jersey dairy cows. Forty-eight lactating cows were randomly assigned to one of 4 treatments: (1) control diet (CON), (2) CON with 25 g/d XOS (XOS), (3) CON with 15 g/d EXE (EXE), and (4) CON with 25 g/d XOS and 15 g/d EXE (XOS + EXE). The 60-d experimental period consisted of a 14-d adaptation period and a 46-d sampling period. The enteric CO2 and CH4 emissions and O2 consumption were measured using two GreenFeed units, which were further used to determine the energy utilization efficiency of cows. Results Compared with CON, cows fed XOS, EXE or XOS + EXE significantly (P < 0.05) increased milk yield, true protein and fat concentration, and energy-corrected milk yield (ECM)/DM intake, which could be reflected by the significant improvement (P < 0.05) of dietary NDF and ADF digestibility. The results showed that dietary supplementation of XOS, EXE or XOS + EXE significantly (P < 0.05) reduced CH4 emission, CH4/milk yield, and CH4/ECM. Furthermore, cows fed XOS demonstrated highest (P < 0.05) metabolizable energy intake, milk energy output but lowest (P < 0.05) of CH4 energy output and CH4 energy output as a proportion of gross energy intake compared with the remaining treatments. Conclusions Dietary supplementary of XOS, EXE or combination of XOS and EXE contributed to the improvement of lactation performance, nutrient digestibility, and energy utilization efficiency, as well as reduction of enteric CH4 emissions of lactating Jersey cows. This promising mitigation method may need further research to validate its long-term effect and mode of action for dairy cows.